Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To determine which option represents the formula for the given arithmetic sequence [tex]\(-20, -16, -12, -8, -4, \ldots\)[/tex], we need to examine the pattern and properties of arithmetic sequences.
1. Identify the first term and common difference:
- The first term ([tex]\(a_1\)[/tex]) of the sequence is [tex]\(-20\)[/tex].
- The sequence progresses as follows:
[tex]\[ -20, -16, -12, -8, -4, \ldots \][/tex]
- To find the common difference ([tex]\(d\)[/tex]), we subtract the first term from the second term:
[tex]\[ d = -16 - (-20) = -16 + 20 = 4 \][/tex]
- Thus, the common difference is [tex]\(4\)[/tex].
2. General formula for the [tex]\(n\)[/tex]-th term of an arithmetic sequence:
- The [tex]\(n\)[/tex]-th term ([tex]\(a_n\)[/tex]) of an arithmetic sequence is given by:
[tex]\[ a_n = a_1 + (n-1)d \][/tex]
- Substituting the values we found:
[tex]\[ a_n = -20 + (n-1)(4) \][/tex]
3. Verify each option against this formula:
- Let's check each given function to see which one matches this form.
- Option 1: [tex]\(f(n) = -20 - 4(n-1)\)[/tex]
- Plug in [tex]\(n=1\)[/tex]:
[tex]\[ f(1) = -20 - 4(1-1) = -20 - 4 \cdot 0 = -20 \][/tex]
- Plug in [tex]\(n=2\)[/tex]:
[tex]\[ f(2) = -20 - 4(2-1) = -20 - 4 \cdot 1 = -24 \][/tex]
- The second term [tex]\(-24\)[/tex] does not match the sequence.
- Option 2: [tex]\(f(n) = -20 + 4(n-1)\)[/tex]
- Plug in [tex]\(n=1\)[/tex]:
[tex]\[ f(1) = -20 + 4(1-1) = -20 + 4 \cdot 0 = -20 \][/tex]
- Plug in [tex]\(n=2\)[/tex]:
[tex]\[ f(2) = -20 + 4(2-1) = -20 + 4 \cdot 1 = -16 \][/tex]
- The second term [tex]\(-16\)[/tex] matches the sequence.
- Option 3: [tex]\(f(n) = -20 - 4(n+1)\)[/tex]
- Plug in [tex]\(n=1\)[/tex]:
[tex]\[ f(1) = -20 - 4(1+1) = -20 - 8 = -28 \][/tex]
- The first term [tex]\(-28\)[/tex] does not match the sequence.
- Option 4: [tex]\(f(n) = -20 + 4(n+1)\)[/tex]
- Plug in [tex]\(n=1\)[/tex]:
[tex]\[ f(1) = -20 + 4(1+1) = -20 + 8 = -12 \][/tex]
- The first term [tex]\(-12\)[/tex] does not match the sequence.
Upon verification, Option 2 [tex]\(f(n) = -20 + 4(n-1)\)[/tex] matches the given arithmetic sequence correctly.
Therefore, the correct formula for the sequence is:
[tex]\[ \boxed{2} \][/tex]
1. Identify the first term and common difference:
- The first term ([tex]\(a_1\)[/tex]) of the sequence is [tex]\(-20\)[/tex].
- The sequence progresses as follows:
[tex]\[ -20, -16, -12, -8, -4, \ldots \][/tex]
- To find the common difference ([tex]\(d\)[/tex]), we subtract the first term from the second term:
[tex]\[ d = -16 - (-20) = -16 + 20 = 4 \][/tex]
- Thus, the common difference is [tex]\(4\)[/tex].
2. General formula for the [tex]\(n\)[/tex]-th term of an arithmetic sequence:
- The [tex]\(n\)[/tex]-th term ([tex]\(a_n\)[/tex]) of an arithmetic sequence is given by:
[tex]\[ a_n = a_1 + (n-1)d \][/tex]
- Substituting the values we found:
[tex]\[ a_n = -20 + (n-1)(4) \][/tex]
3. Verify each option against this formula:
- Let's check each given function to see which one matches this form.
- Option 1: [tex]\(f(n) = -20 - 4(n-1)\)[/tex]
- Plug in [tex]\(n=1\)[/tex]:
[tex]\[ f(1) = -20 - 4(1-1) = -20 - 4 \cdot 0 = -20 \][/tex]
- Plug in [tex]\(n=2\)[/tex]:
[tex]\[ f(2) = -20 - 4(2-1) = -20 - 4 \cdot 1 = -24 \][/tex]
- The second term [tex]\(-24\)[/tex] does not match the sequence.
- Option 2: [tex]\(f(n) = -20 + 4(n-1)\)[/tex]
- Plug in [tex]\(n=1\)[/tex]:
[tex]\[ f(1) = -20 + 4(1-1) = -20 + 4 \cdot 0 = -20 \][/tex]
- Plug in [tex]\(n=2\)[/tex]:
[tex]\[ f(2) = -20 + 4(2-1) = -20 + 4 \cdot 1 = -16 \][/tex]
- The second term [tex]\(-16\)[/tex] matches the sequence.
- Option 3: [tex]\(f(n) = -20 - 4(n+1)\)[/tex]
- Plug in [tex]\(n=1\)[/tex]:
[tex]\[ f(1) = -20 - 4(1+1) = -20 - 8 = -28 \][/tex]
- The first term [tex]\(-28\)[/tex] does not match the sequence.
- Option 4: [tex]\(f(n) = -20 + 4(n+1)\)[/tex]
- Plug in [tex]\(n=1\)[/tex]:
[tex]\[ f(1) = -20 + 4(1+1) = -20 + 8 = -12 \][/tex]
- The first term [tex]\(-12\)[/tex] does not match the sequence.
Upon verification, Option 2 [tex]\(f(n) = -20 + 4(n-1)\)[/tex] matches the given arithmetic sequence correctly.
Therefore, the correct formula for the sequence is:
[tex]\[ \boxed{2} \][/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.